Workload Analysis Pada Operator Mesin Trulaser Trumpf 3030 Di Pt. Xyz Menggunakan Metode Full Time Equivalent (Fte) - Bintara Putra Dicya; Endang Pudji Widjajati (Jurnal Kendali Teknik dan Sains, 2024)
This research aims to analyze the workload of TruLaser Trumpf 3030 machine operators at PT. XZY using the Full Time Equivalent (FTE) Method. Data collection was carried out through interviews, direct observation, and lead time measurements in the Preparation Department, especially on the Trumpf TruLaser 3030 Machine. The results of the analysis showed variations in FTE values ​​over 3 days for 1 machine operator for 8 working hours. Although the majority of FTE values ​​are below the overload value, there is one case where the FTE value on September 20 2023 is 0.861, below the required standard. The conclusion shows that there is no problem of work overload for the Trumpf TruLaser 3030 machine operator, however, overtime or overtime is planned by the PPIC/Planner team to achieve production targets. Factors such as machine speed, machine errors, equipment delays, and hampered production processes cause operator idle time. The recommended solution is to maintain and repair machines regularly, plan a more efficient work flow, prepare materials well, improve facilities for material handling, and carefully plan the production process. To overcome idle time, it is recommended to provide additional work such as training for interns or administrative work during shift changes or the next day.